Medical Requirements During a Natural Disaster: A Case Study on WhatsApp Chats Among Medical Personnel During the 2015 Nepal Earthquake. (13th June 2017) - Basu, Moumita; Ghosh, Saptarshi; Jana, Arnab; Bandyopadhyay, Somprakash; Singh, Ravikant
ABSTRACT: Objective: The objective of this study was to explore a log of WhatsApp messages exchanged among members of the health care group Doctors For You (DFY) while they were providing medical relief in the aftermath of the Nepal earthquake in April 2015. Our motivation was to identify medical resource requirements during a disaster in order to help government agencies and other responding organizations to be better prepared in any upcoming disaster. Methods: A large set of WhatsApp (WhatsApp Inc, Mountain View, CA) messages exchanged among DFY members during the Nepal earthquake was collected and analyzed to identify the medical resource requirements during different phases of relief operations. Results: The study revealed detailed phase-wise requirements for various types of medical resources, including medicines, medical equipment, and medical personnel. The data also reflected some of the problems faced by the medical relief workers in the earthquake-affected region. Conclusions: The insights from this study may help not only the Nepalese government, but also authorities in other earthquake-prone regions of the world to better prepare for similar disasters in the future. Moreover, real-time analysis of such online data during a disaster would aid decision-makers in dynamically formulating resource-mapping strategies. ( Disaster Med Public Health Preparedness . 2017;11:652–655).